INTERROGATING THE EFFECTS OF SAND MINING: A CASE STUDY OF AGILA DISTRICT, ADO LOCAL GOVERNMENT AREA, BENUE STATE, NIGERIA - Baba Aminu, Mu'awiya; Kabiru, Garba Ilelah; Simon, Dalom Christopher; Changde, Andrew Nanfa; Andarawus, Yohanna; Nengak, Musa; Balogun, Frankie Ojo; Ahmad, Tijjani Dahiru; Akagbue, Bertha Onyenachi; Simon, Tobias; Oseigbovo, Favour Ofure; Paca, Francisco Soki; et al. (FUDMA JOURNAL OF SCIENCES, 2023)
This study is of believe that Illegal acts and discerning sand excavation/mining has become arisk to the ambiances. While theresearchrelied on personal geological observation on the mining sites, qualitative data were used from secondary literature. Using Agila’s river and coastal mining sites as a case study, the study revealed that it sparks to diversifications in river channels ways, physical ecosystem and food webs. As well it speeds up the river’scurrent and eventually eroding the river banks. Destroying the soil profile and removing the flora reduces the population of animals and eliminates habitat both the surface and subsurface resources. Sand dunes has played a vital aspect role in stoppage against heavy storms, erosion causes by some agents of transportations like winds, waves or floods. Numerous tiny habitants that are a component of the marine and coastal food chain and whose removal would pose some hazards to some other species rely on them for existence. The water tables in the surrounding areas decline as a result of sand mining, drying out the drinking water wells on the river embankments. Turbidity rises at the mining site as also the aquifers near the shore are affected by saline water intrusion. Sand mined areas loose scenic beauty, it emits radiation reliant on the component minerals, dust pollution, emits vibration/noise and it damages roads and some infrastructures. This researchinspected and reviewed the sand mining impacts on river, dune, marine, hydrological, biological and sociological environments with some case studies of the study area.